1989
DOI: 10.1056/nejm198911233212104
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Desmopressin (1-Desamino-8-D-Arginine Vasopressin) to Reduce Blood Loss in Uncomplicated Cardiac Surgery

Abstract: Previous studies have suggested that desmopressin may reduce the bleeding diathesis that often complicates open-heart surgery. To pursue this question further, we performed a double-blind, randomized, placebo-controlled trial to determine whether the previously reported beneficial effect of desmopressin on hemostasis during complex cardiac surgery was applicable to all elective cardiac surgical procedures involving cardiopulmonary bypass. In 150 consecutive patients, most of whom underwent primary coronary-art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(60 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin. 30,38,40,41,44,46,48,50,56,…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin. 30,38,40,41,44,46,48,50,56,…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…26 In a randomized trial comparing DDAVP versus placebo, we could not confirm that DDAVP reduces the total blood loss and transfusion requirements, although it was observed to significantly reduce intraoperative blood loss. 16 These results were later confirmed by Hackmann et al 27 Furthermore, four additional studies did not find significant improvement in postoperative blood loss,28-31 and one report shows that the total postoperative blood loss and the red cell transfusion rates were significantly higher in the DDAVP group than in the control group, which could be related to the DDAVP-induced TPA release from endothelial cells and subsequent fibrinolysis. 32 Since, as suggested by our findings, the administration of DDAVP was effective only in reducing intraoperative bleeding, we decided to administer a second dose 6 hours after surgery to establish whether it could also improve the postoperative blood loss.…”
Section: Discussionmentioning
confidence: 82%
“…100 Further studies have not supported this advantage. [101][102][103] Seear found no difference in blood loss when comparing DDAVP with placebo in children. 104 DDAVP at 0.3 µg/kg showed a maximal increase in FVIII:vWF in adults.…”
Section: Desmopressinmentioning
confidence: 99%